A Novel RNA-Binding Protein Involves ABA Signaling by Post-transcriptionally Repressing ABI2 - Xu, Jianwen; Chen, Yihan; Qian, Luofeng; Mu, Rong; Yuan, Xi; Fang, Huimin; Huang, Xi; Xu, Enshun; Zhang, Hongsheng; Huang, Ji (Frontiers in Plant Science, 2017)
The Stress Associated RNA-binding protein 1 (SRP1) repressed by ABA, salt and cold encodes a C2C2-type zinc finger protein in Arabidopsis. The knock-out mutation in srp1 reduced the sensitivity of seed to ABA and salt stress during germination and post-germinative growth stages. In contrast, SRP1-overexpressing seedlings were more sensitive to ABA and salt compared to wild type plants. In the presence of ABA, the transcript levels of ABA signaling and germination-related genes including ABI3, ABI5, EM1 and EM6 were less induced in srp1 compared to WT. Interestingly, expression of ABI2 encoding a protein phosphatase 2C protein were significantly up-regulated in srp1 mutants. By in vitro analysis, SRP1 was identified as a novel RNA-binding protein directly binding to 3’UTR of ABI2 mRNA. Moreover, transient expression assay proved the function of SRP1 in reducing the activity of luciferase whose coding sequence was fused with the ABI2 3’UTR. Together, it is suggested that SRP1 is involved in the ABA signaling by post-transcriptionally repressing ABI2 expression in Arabidopsis.